PENGARUH MODAL KERJA, ASET DAN SUKU BUNGA TERHADAP PERTUMBUHAN LABA PADA PT. PATI SARI MEDAN PERIODE 2013 - 2017 - WILSON .; MEGA RAYANI; DINA ROSMANELIANA; REBECCA EVADINE SIAHAAN (JURNAL ILMIAH KOHESI, 2018)
The purpose of this study is to find out the effect of working capital, assets and interest rates on profit growth in PT. Pati SariMedan. The results showed working capital, assets and interest rates simultaneously had a positive and significant effect onprofit growth in PT. Pati Sari Medan Period 2013-2017. In the coefficient of determination (Adjusted R2) variations in workingcapital variables, assets and interest rates while the rest of (100% - 11.5%= 88.5%) is another variation of variables notdescribed in this study such as cash turnover, and others. Working Capital partially has no significant effect on Profit Growthin PT. Pati Sari Medan Period 2013-2017. Assets partially have no significant effect on profit growth in PT. Pati Sari MedanPeriod 2013-2017. Interest Rates partially have a positive and significant effect on profit growth in PT. Pati Sari MedanPeriod 2013-2017.